Chemically Synthesized Bi0.76sb1.24s3 Photoelectrodes for Photoelectrochemical Water Splitting - Radhalayam, D (Elsevier Ltd, 2025)
Developing a simple, efficient, and cost-effective photoelectrode is crucial for improving photoelectrochemical (PEC) performance. In this study, we chemically synthesized Bi0.76Sb1.24S3 photoelectrodes followed by annealing at 300–500 °C. The as-grown photoelectrode initially exhibited an amorphous structure with a bandgap of 1.9 eV. Annealing the photoelectrode at 300 °C led to the emergence of an orthorhombic Bi0.76Sb1.24S3 phase alongside a secondary InSbS3 phase, reducing the bandgap to 1.52 eV. Increasing the temperature to 350–450 °C promoted the growth of the InSbS3 phase and further lowered the bandgap to 1.42 eV. At 500 °C, InSbS3 became the dominant phase, further reducing the bandgap to 1.37 eV. Photocurrent density measurements in a PEC cell revealed a photocurrent of 2 mA/cm2 for films annealed in the range of 300–400 °C, which decreased to 1.3 mA/cm2 at 450 °C. Notably, the Bi0.76Sb1.24S3 photoelectrode annealed at 350 °C exhibited the highest and most stable photocurrent over 630 s. This study demonstrates a simple and cost-effective route for preparing Bi0.76Sb1.24S3 photoanodes, offering promising potential for efficient PEC water-splitting applications. © 2025 International Solar Energy Society